"Мама, почему у меня синдром Дауна?" - Филпс Каролина (Любовь изгоняет страх, 2012)
Экземпляры: аб. (2012) / Инвентарный номер: 54499 / Цена: / Сис.шифр: 57.33 / Авт.знак: Ф 56 / ГРНТИ: 76.01 / ББК: 57.33я91